Coca-Cola Transfer Pricing Dispute: United States Case Analysis and Tax Policy Lessons for Indonesia - Agus Suharsono; Nanik Prasetyoningsih (MultiTech Publisher, 2024)
Decision of the Coca-Cola transfer pricing dispute in the United States Tax Court, which resulted in tax underpayment, can be used as a lesson for Indonesia. This research method is doctrinal, with a law, case, concept and interpretation approach. The data studied is secondary data in the form of laws, cases and relevant references, which are analyzed to obtain conclusions and recommendations. Research shows that the court considered using the Comparable Profits Method by tax authorities to evaluate the profitability of The Coca-Cola Company's supply points, given the difficulty of valuing intangible assets directly and the need for disproportionate profit adjustments. To avoid similar problems, companies in Indonesia must use transfer pricing methods that are reliable and appropriate to local conditions, as well as ensure good intellectual property management and documentation transparency, while tax authorities must monitor transactions between affiliated entities by international standards and the Arm's Length Principle.